Amelioration of pregnancy outcomes in a pregnant rat model with deep venous thrombosis following the transplantation of bone marrow mesenchymal stem cells - Xie, Yuanyuan; Zhang, Junrong; Du, Rong; Ji, Jingjing; Lu, Jingjing; Li, Haoxuan; Xu, Yunzhao; Zhang, Yuquan; Cheng, Xi (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveWe investigated the effects of bone marrow mesenchymal stem cells (BM-MSCs) on pregnancy outcomes in pregnant Sprague-Dawley rats with deep venous thrombosis (DVT) and explored the potential mechanisms involved.MethodsEighteen pregnant rats were randomly divided into three groups: sham, DVT and BM-MSCs. The BM-MSCs were transfected with lentivirus carrying luciferase and cell membrane staining reagent CM-Dil to analyze the location and survival of BM-MSCs in vivo. We also compared the weight and length of the thrombus, the embryo absorption rate, the complete blood count, coagulation function, and D-dimer concentration of pregnant rats between the groups. Thereafter, placental blood flow was monitored by Doppler ultrasound and the number of placental blood vessels was determined by CD31 staining 7 days following BM-MSC transplantation. Finally, the expression of placental growth factor (PlGF), vascular endothelial growth factor A (VEGFA), soluble fms-like tyrosine kinase 1 (sFlt1), VEGF receptor 2 (VEGFR2) both in mRNA and protein levels were detected.ResultsReduced thrombus and improved pregnancy outcomes were observed in the BM-MSCs group. Furthermore, BM-MSCs survived and migrated to the lungs, liver, spleen, and thrombotic tissues, rather than the placenta. Doppler ultrasound indicated insufficient placental perfusion in the DVT group, which was reversed by the transplantation of BM-MSCs. BM-MSCs promoted placental angiogenesis by upregulating VEGFA and VEGFR2, and by reducing sFlt1 protein levels in the placenta.ConclusionOur analysis suggested that BM-MSCs improve pregnancy outcomes associated with obstetric DVT by alleviating placental hypoperfusion and regulating the balance of placental pro-/anti-angiogenic factors.